Air pollution: cardiovascular and other negative effects on pregnancy: a narrative review - Leen Van den Eeden; Greet Leysens; Dominique Mannaerts; Yves Jacquemyn (IMR Press, 2021)
Objectives: The main goal of this narrative review is to summarize the data on the relationship between air pollution and pregnancy outcome. Mechanism: The authors conducted a critical but concise review on published studies relating to particulate matter (PM2.5 and PM10), carbon monoxide, ozone and nitrogen oxide versus pregnancy outcome. Findings in brief: (Over) exposure to particulate matter is associated with a negative outcome on fertility and early pregnancy loss. There is an increased risk of congenital birth anomalies, birth weight and pregnancy-induced hypertensive disorders with exposure on PM2.5. Exposure to ozone and NO2 decreases the chance of live birth rate and increases the risk of congenital heart diseases, preterm birth and hypertensive disorders. Conclusions: Air pollution is traditionally correlated with adverse health effects. In the current review, we concisely but critically compile the most relevant studies on pregnancy-related effects. Particulate matter, carbon monoxide, ozone, and nitrogen dioxide are the key air pollutants. Exposure to these pollutants has been associated with cardiovascular disease, respiratory disease, and negative effects on pregnancy.